2020
DOI: 10.1111/jar.12792
|View full text |Cite
|
Sign up to set email alerts
|

Intervention effects on professionals’ attitudes towards the participation of adults with visual and severe or profound intellectual disabilities

Abstract: Participation is a human right for people with disabilities (UN General Assembly, 2013), including adults with visual and severe or profound intellectual disabilities (VSPID). Participation enhances the quality of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 22 publications
0
11
1
4
Order By: Relevance
“…Second, CFP+ may simply not lead to an improvement in the participation of adults with VSPID. However, this finding is not supported by findings in our earlier studies, which revealed that the range of activities that encouraged the social relations, inclusion and autonomy of participating adults with VSPID had increased (Hanzen et al, 2016;Hanzen et al, 2020b). In addition, the increases in the active involvement of the individuals with VSPID and in the DSPs' initiatives in the CFP+ group, relative to the control groups, as shown in the current study, were indicative of the positive effects of CFP+ on the participation of the target group.…”
Section: Discussioncontrasting
confidence: 73%
See 4 more Smart Citations
“…Second, CFP+ may simply not lead to an improvement in the participation of adults with VSPID. However, this finding is not supported by findings in our earlier studies, which revealed that the range of activities that encouraged the social relations, inclusion and autonomy of participating adults with VSPID had increased (Hanzen et al, 2016;Hanzen et al, 2020b). In addition, the increases in the active involvement of the individuals with VSPID and in the DSPs' initiatives in the CFP+ group, relative to the control groups, as shown in the current study, were indicative of the positive effects of CFP+ on the participation of the target group.…”
Section: Discussioncontrasting
confidence: 73%
“…DSPs in the second control group provided care as usual. A process evaluation conducted for the above study revealed that DSPs applied CFP+ when attempting to develop new roles and activities for the targeted individuals and to promote their self-management, autonomy, and active involvement in existing activities (Hanzen et al, 2020b). The evaluation further revealed that the DSPs' attitudes toward participation improved after they had received CFP+ training.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations